2013
DOI: 10.1016/j.ajpath.2013.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Transitions of Macrophages Orchestrate Tissue Repair

Abstract: Macrophages are essential for the efficient healing of numerous tissues, and they contribute to impaired healing and fibrosis. Tissue repair proceeds through overlapping phases of inflammation, proliferation, and remodeling, and macrophages are present throughout this progression. Macrophages exhibit transitions in phenotype and function as tissue repair progresses, although the precise factors regulating these transitions remain poorly defined. In efficiently healing injuries, macrophages present during a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
239
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(248 citation statements)
references
References 97 publications
4
239
1
1
Order By: Relevance
“…Recognition that effector cells of the immune system, such as the macrophages and Thelper cells, not only promote classic inflammatory processes but also orchestrate the temporal inhibition of inflammation and initiation of functional tissue remodeling [25,31,42,43,44,45] provides the opportunity to re-examine immunosuppressive strategies for treatment of diseases such as UC. Although the signaling molecules that influence macrophage and lymphocyte phenotype transition are not fully understood, there is suggestive evidence that at least some of these regulators reside within the ECM [9,10,25].…”
Section: Discussionmentioning
confidence: 99%
“…Recognition that effector cells of the immune system, such as the macrophages and Thelper cells, not only promote classic inflammatory processes but also orchestrate the temporal inhibition of inflammation and initiation of functional tissue remodeling [25,31,42,43,44,45] provides the opportunity to re-examine immunosuppressive strategies for treatment of diseases such as UC. Although the signaling molecules that influence macrophage and lymphocyte phenotype transition are not fully understood, there is suggestive evidence that at least some of these regulators reside within the ECM [9,10,25].…”
Section: Discussionmentioning
confidence: 99%
“…2 Macrophages undergo phenotypic and functional changes in each phase, and this ''functional plasticity'' leads to efficient wound healing and tissue repair after injury. 2 However, dysregulated macrophage activation can lead to impaired healing responses and chronic inflammation in several disease states.…”
Section: Introductionmentioning
confidence: 99%
“…2 Macrophages undergo phenotypic and functional changes in each phase, and this ''functional plasticity'' leads to efficient wound healing and tissue repair after injury. 2 However, dysregulated macrophage activation can lead to impaired healing responses and chronic inflammation in several disease states. 2 Microglia are the primary immune cells in the brain, and despite their distinct origin, 3 they share many phenotypic and functional properties with macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Macrophages of M2c type express high levels of cluster of differentiation 163 (CD163), which has been shown to be associated with tissue repair and remodeling of the wound and promoting cell proliferation in mice. 13 In 2004, Lau et al 14 reported that CD163 immunoreactivity was observed in resident macrophages of all normal tissue samples including lymph node and tonsil, red pulp macrophages of spleen, bone marrow, alveolar macrophages of the lung, and Kupffer cells of the liver. CD163 is not expressed in splenic white pulp macrophages and germinal center tingible body macrophages.…”
Section: Introductionmentioning
confidence: 99%